EFEKTIVITAS MODEL NHT & PPBL TERHADAP MOTIVASI BELAJAR TEMATIK SISWA KELAS 4 SD - Yeni Syafiatun; Naniek Sulistya Wardani; Tego Prasetyo (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aims to determine whether there is effectiveness of Numbered Heads Together (NHT) model and Problem Based Learning (PPBL) approach to the motivation of thematic learning of grade 4 elementary school students. The type of research used is quasi experimental research. The sampling technique used purposive stratified disproportionate sampling technique. This data analysis technique using average difference test (t test). The normality of the experimental group is 0.243> 0.05 and the control group is 0.438> 0.05, the two groups are normally distributed. The homogeneity of the experimental group and the control group was 0.595> 0.05, the experimental group and the control group were homogeneous. The results showed t count 8.564> t table 1.997, then Ha accepted means there is the effectiveness of NHT and PPBL models on the motivation of thematic learning 4th grade elementary school students. Significance of 0.000 <0,05, then Ha accepted means there is effectiveness of NHT model and PPBL to motivation of thematic learning of 4th grade elementary school students meaningful. The mean of experimental learning motivation of experiment group is 49,88 and control group equal to 41,38. The average difference between thematic motivation of experimental group and control group is 8.5. The advice given is that teachers are expected to use the NHT and PPBL models in designing the lesson, so that the thematic learning motivation can be improved.Keywords: Model of NHT and PPBL, Thematic Learning Motivation, Thematic Learning